Effects of Nature-Based Intervention in Occupational Health Care on Stress – A Finnish Pilot Study Comparing Stress Evaluation Methods - Lipponen, Maija; Hallikainen, Ville; Kilpeläinen, Pekka (Informa UK Limited, 2022)
Nature has many favorable impacts on well-being. Nature-based programs create an interesting new way to support people’s social, physical and mental health. At occupational health care nature environments are not widely used so far. In this study we aimed to try out a simple program suitable for occupational health care, to test and compare methods for monitoring stress and to evaluate sources of interfering factors. We noticed that participants’ salivary cortisol levels got lower on intervention days compared to days without intervention. We also found that salivary α-amylase increased during the intervention, but the increase was lower every time in consecutive appointments. They both are well-known stress markers. Other measures were heart rate variability and two self-reported questionnaires to assess the impacts over the study period. There were slight changes in these indices, but the difference was not significant. Because of small sample size, lack of a control group and other limiting conditions, the results are only indicative, but they are supported by the feedback from participants and health care professionals who experienced NBI as a good tool to promote well-being at work and free time. For future studies there is a need for several stress monitoring methods to obtain reliable overview on the effects of nature-based health care methods.
Keywords: salivary cortisol; salivary α-amylase; heart rate variability; pain; work exhaustion